From Loss to Survival: A study on the Sumbanese Women’s Experiences during Covid-19 Mitigation - Meylani Yo; Pupu Purwaningsih (Jurnal Perempuan, 2020)
AbstrakArtikel ini menggambarkan kemampuan bertahan dan beradaptasi perempuan Sumba, sebagai kelompok rentan, saat pandemi COVID-19 mengubah perilaku dan pola hidup mereka sebagai dampak dari pengendalian pandemi COVID-19. Pengendalian pandemi berdampak langsung terhadap interaksi dan relasi sosial, pekerjaan, penghayatan iman, harapan atas masa depan anak-anak hasil pendidikan online serta stigmatisasi terhadap mereka yang tidak menjalankan protokol kesehatan untuk mencegah penularan COVID-19. Dengan keterbatasan waktu dan kondisi pandemi, metode penelitian yang digunakan dalam penelitian adalah kualitatif dengan teknik penggumpulan data melalui wawancara mendalam per telpon (1 informan), diskusi kelompok terfokus daring (4 partisipan) dan survei daring dengan pertanyaan terbuka yang melibatkan 17 responden di Sumba. Metode tersebut dilengkapi dengan pemahaman mendalam atas konteks harian responden karena salah satu peneliti tinggal di kota Sumba dan mengenal para responden.  Kata kunci: ketahanan, relasi sosial, stigmatisasi, perempuan Sumba, COVID-19.   AbstractThis study describes the ability of Sumbanese women, as a vulnerable group, to adapt and to be resilient during the global pandemic of COVID-19 that has changed their behavior and lifestyle due to the impacts of mitigation strategy of COVID-19. The mitigation of this global pandemic has been creating direct impacts on social relation and interaction, jobs, faith and religious practices, hope of children’s future as a result of online education, as well as public stigma of persons who are disobeying COVID-19 prevention protocols. This study adopts qualitative research method. Due to time limitation and the situation of pandemic, the data collection techniques are done online which involved 18 informants. This includes an open survey with 17 respondents, in-depth interview with 1 informant by telephone. An online focus group discussion was later conducted to clarify data and to seek further information from 4 respondents. This method is complemented by a deep understanding of the daily life of respondents since one of the researchers currently lives in Weetebula and is very familiar with some respondents.Keywords: resilience, social relation, stigmatisation, Sumbanese women, COVID-19.